Beitrag zur Morphologie und Entwicklung von Liriomyza spec., einem schädlichen Minierer an Phaeseolus vulgaris L. in Kuba. - Fröhlich, Gerd; Richter, Siegfried (Contributions to Entomology = Beiträge zur Entomologie, 1987)
The bean leaf miner Liriomyza spec., must be regarded as a serious pest threatening the cultivation of Phaseolus vulgaris L. in Cuba. The feeding of the grubs on the leaves can cause a considerable loss of assimilation surface especially of young plants. Studies on the morphology of the adults and their stages of development and on the habit and development of the genus Liriomyza Mik are presented.